Factors Influencing the Prioritization of Injured Patients for Transfer to a Burn or Trauma Center Following a Mass Casualty Event. (3rd February 2021) - Lancet, Elizabeth A.; Zhang, Wei Wei; Roblin, Patricia; Arquilla, Bonnie; Zeig-Owens, Rachel; Asaeda, Glenn; Kaufman, Brad; Alexandrou, Nikolaos A.; Gallagher, James J.; Cooper, Michael L.; Styles, Timothy; Prezant, David J.; et al.
ABSTRACT: Objectives: In New York City, a multi-disciplinary Mass Casualty Consultation team is proposed to support prioritization of patients for coordinated inter-facility transfer after a large-scale mass casualty event. This study examines factors that influence consultation team prioritization decisions. Methods: As part of a multi-hospital functional exercise, 2 teams prioritized the same set of 69 patient profiles. Prioritization decisions were compared between teams. Agreement between teams was assessed based on patient profile demographics and injury severity. An investigator interviewed team leaders to determine reasons for discordant transfer decisions. Results: The 2 teams differed significantly in the total number of transfers recommended (49 vs 36; P = 0.003). However, there was substantial agreement when recommending transfer to burn centers, with 85.5% agreement and inter-rater reliability of 0.67 (confidence interval: 0.49–0.85). There was better agreement for patients with a higher acuity of injuries. Based on interviews, the most common reason for discordance was insider knowledge of the local community hospital and its capabilities. Conclusions: A multi-disciplinary Mass Casualty Consultation team was able to rapidly prioritize patients for coordinated secondary transfer using limited clinical information. Training for consultation teams should emphasize guidelines for transfer based on existing services at sending and receiving hospitals, as knowledge of local community hospital capabilities influence physician decision-making.